Legal Protections Accorded to Persons with Disabilities under Ethiopian Law - Admasu, Belayneh (Bahir Dar University Journal of Law, 2022)
Persons with disabilities are marginalized members of society who do not fullyand effectively participate in socio-economic activities on an equal basis withothers due to various barriers in the environment. Taking this into account, theUnited Nations has promulgated the Convention on the Rights of Persons withDisabilities, which complements general human rights instruments and givesparticular emphasis to respect and protection of the rights of persons withdisabilities. As a member state, Ethiopia ratified the convention and enactedother domestic laws to ensure equality before the law and benefits for personswith disabilities. This article appraises these laws in order to examine the levelof protection accorded to persons with disabilities in Ethiopia. For thispurpose, the article gives emphasis to the rights to equality and nondiscrimination, access to the environment, information and communication,employment, and tertiary education.